Pisa syndrome in dementia with Lewy bodies: A Chinese multicenter study. (October 2022) - Su, Zhou; Liu, Shuai; Chen, Gang; Gan, Jinghuan; Bao, Xinran; Zhu, Hongcan; Wang, Xiaodan; Wu, Hao; Ji, Yong
Abstract: Background: Pisa syndrome (PS) is rarely reported in Dementia with Lewy bodies (DLB). The aim of this article is to investigate the prevalence rate of PS and the correlation with clinical features evaluated in patients with DLB. Methods: A total of 209 DLB patients were consecutively recruited and underwent standardized clinical evaluation in our multicenter study. The associations between PS and clinical factors were evaluated. Results: The prevalence rate of PS in patients with DLB was 15.3%, which was higher in the moderate and severe stages than mild cognitive impairment and mild stages (81.2% vs. 18.8%). Patients with PS had a longer duration of disease ( P  = 0.020) and parkinsonism ( P  = 0.003), higher scores of NPI ( P  = 0.028), ADL ( P  = 0.002) and UPDRS part III ( P  < 0.001), lower scores of clock drawing test ( P  = 0.009), visuospatial/executive abilities ( P  = 0.018), attention ( P  = 0.020), language and praxis ( P  = 0.020), registration ( P  = 0.012 ), greater H&Y stage ( P  < 0.001), and higher proportion of cholinesterase inhibitors used ( P  = 0.044) than those without PS. Longer disease duration (OR = 1.166, P  = 0.023), presence of parkinsonism (OR = 7.971, P  = 0.007), moderate and severe dementia (OR = 3.215, P  = 0.021) were associated with the presence of PS. Patients had a longer duration of PS ( P  = 0.014) and lower mean age of onset ( P  = 0.040) in the group with severe lateral trunk flexion . Conclusion: The development of PS may be associated with longer disease duration, the presence of parkinsonism and severe stages of dementia in DLB. Cholinesterase inhibitors may have a correlation with PS. The severity of lateral flexion is related to the duration of PS and mean age of onset. Highlights: This is the first study to investigate the prevalence rate of PS and the correlation with clinical features evaluated in patients with DLB. The development of PS may be associated with longer disease duration, the presence of parkinsonism and severe stages of dementia in DLB. Cholinesterase inhibitors may have a correlation with PS and the severity of lateral flexion is related to the duration of PS and the mean age of onset.